Preliminary Study on Game-Based Learning to Promote Javan Leopard Conservation: Perspectives from Prospective Biology Teachers - Diki Muhamad Chaidir; Suprapto, Purwati Kuswarini; Liah Badriah; Dani Ramdani (SEAQIS Journal of Science Education, 2025)
Research on game-based learning has been widely conducted to support biology education in the classroom. This type of learning should also have an additional impact on students, one of which is introducing endangered species, such as the Javan leopard (Panthera pardus melas). This study explores the initial stage of developing Game-Based Learning (GBL) media and its impact on prospective biology teachers' interest, attitude, and knowledge regarding Javan leopard conservation. The research method used a quantitative and qualitative approach, with a survey comprising both open and closed-ended questions to assess the responses of prospective biology teachers to the biology game application focused on ecological communities. Interest was measured on a Likert scale; attitudes were measured through multiple-choice and agreement-scale questions; and knowledge was assessed through multiple-choice and true/false questions, while open-ended questions were applied for suggestions and recommendations from GBL. The respondents were 108 students who had previously tested the developed application. In the data analysis, descriptive statistical methods were used to interpret quantitative data, while qualitative analysis was conducted using word clouds to depict the answers of prospective biology teacher students in open-ended questions. The demographic data revealed that 73% of students typically play games for less than 1 hour per week, 72% play online games, and adventure is the most frequently played genre. Additionally, 92% of students had never played a game related to leopards before, and only about 27.1% of students had prior knowledge about leopards, mostly from their teachers at school. After using the application, 68% of students expressed increased interest in leopard conservation, improved knowledge, and demonstrated a positive attitude. Furthermore, 88% of students felt that the game helped raise their awareness of leopard conservation. This study concludes that game-based learning, which integrates information about endangered species like the Javan leopard, has enormous potential to support biology education and raise awareness of biodiversity conservation.